Web-Based Geographic Information System for Landslide Prone Areas in Bengkulu Province - Diana Diana; Shinta Indriyani (Jurnal Komputer, Informasi dan Teknologi, 2022)
Bengkulu Province is one of the areas prone to disasters.Based on the data from Regional Disaster Management Agency (BPBD) in year 2020,eight of ten regencies in Bengkulu province are included in the high risk class for landslides, and two others are in the medium class.The lack of information received by the community about the location of the landslide disaster resulted in a high level losses suffered by them, both human and material casualties.Therefore, a web-based geographic infomartion system application was made.The existence of GIS combined with web design and web mapping is expected to be a means to facilitate the delivery of relevant and approprite information for all parties that need it.The results of the study indicate that the application can run well and display maps and information on the number of landslides per year in all regencies of Bengkulu Province.